Fire resistance of geopolymer concrete: A critical review. (21st March 2022) - Amran, Mugahed; Huang, Shan-Shan; Debbarma, Solomon; Rashid, Raizal S.M.
Highlights: Geopolymer concrete (GPC) is emerging as a promising building material. GPC has the potential to retain its compressive strength under elevated temperatures. Recycled fibers (RFs) are used to enhance the toughness, shrinkage, and cracking resistance of GPC. The addition of RFs is a strategy for overcoming limitations and preventing GPC microstructure deterioration. Future investigations are also delivered for enabling the wide use of RF-RGPC in concrete applications. Abstract: Although a novel inorganic family of geopolymer concrete (GPC) is a promising building material. The need for understanding its resistance against fire at high temperatures is considered essential to ensure its long-term durability. Physical examinations of the degree of cracking, spalling, brittleness, and loss of strength in GPC upon exposure to high temperatures and during fires provide an indicator of their resilience to such conditions. The addition of recycled fibers (RFs) to GPC has been reported as a strategy for overcoming these limitations and preventing concrete microstructure deterioration. Therefore, the development of RF-reinforced GPC (RF-RGPC) to resist fire has become research imperative. The use of RFs derived from industrial wastes provides additional benefits, such as waste reduction, resource conservation, reduced processing costs compared with virgin fibers, and the elimination of waste disposal in landfills. Moreover, RF-RGPC is an inorganic polymer binder made through the alkali activation of reactive aluminosilicate materials that comprise RFs, which increase its structural reliability. In this regard, conducting a critical literature review of current updates related to the fire performance of RF-RGPC subjected to elevated temperatures and during fires is urgently necessary. This study provides critical reviews on the type of RFs, spalling mechanism, physical inspection and properties of RF-RGPCs. It also comprehensively demonstrated the influence of fire on the properties of RF-RGPC after high temperature exposure. The major findings of this study are expected to introduce this unique, cutting-edge, accessible, and environment-friendly RF-RGPC as a promising, durable and heat- and fire-resistant building material for the current infrastructure and sustainable construction industries.